Errata - Flavour components of whiskey. III. Ageing changes in the low-volatility fraction. - Team, Editorial (South African Journal of Enology and Viticulture, 2017)
MacNamara, K., Van Wyk, C.J., Brunerie, P., Augustyn, O.P.H. & Rapp, A., 2001. Flavour components of whiskey. III. Ageing changes in the low-volatility fraction. S. Afr. J. Enol. Vitic. 22, 82-92.